Optimal Cut-Off Value of the Superior Articular Process Area as a Morphological Parameter to Predict Lumbar Foraminal Stenosis. (9th January 2017) - Lim, Tae-Ha; Choi, Soo Il; Cho, Hyung Rae; Kang, Keum Nae; Rhyu, Chang Joon; Chae, Eun Young; Lim, Young Su; Lee, Yongsoo; Kim, Young Uk
Abstract : Background . We devised a new morphological parameter called the superior articular process area (SAPA) to evaluate the connection between lumbar foraminal stenosis (LFS) and the superior articular process. Objective . We hypothesized that the SAPA is an important morphologic parameter in the diagnosis of LFS. Methods . All patients over 60 years of age were included. Data regarding the SAPA were collected from 137 patients with LFS. A total of 167 control subjects underwent lumbar magnetic resonance imaging (MRI) as part of a routine medical examination. We analyzed the cross-sectional area of the bone margin of the superior articular process at the level of L4-L5 facet joint in the axial plane. Results . The average SAPA was96.3 ± 13.6 mm 2 in the control group and128.1 ± 17.2 mm 2 in the LFS group. The LFS group was found to have significantly higher levels of SAPA (p < 0.001 ) in comparison to the control group. In the LFS group, the optimal cut-off value was 112.1 mm 2, with 84.4% sensitivity, 83.9% specificity, and AUC of 0.94 (95% CI: 0.91–0.96). Conclusions . Higher SAPA values were associated with a higher possibility of LFS. These results are important in the evaluation of patients with LFS.